Functional and phylogenetic analyses of tadpole community assembly in temperate montane streams. (February 2023) - Sun, Zijian; Su, Shengqi; Feng, Jianyi; Zhao, Chunlin; Zhu, Wenbo; Fan, Wenbo; Lan, Jing; Zhao, Tian
Highlights: Tadpole diversity varied along an elevational gradient. Tadpole diversity was determined by microhabitat variables. Tadpole community structure was more clustered in the low and high elevational streams. Tadpole community structure was more dispersed in the mid-elevation streams. Abstract: Understanding the spatial patterns and the maintenance of biodiversity is a central target in ecology and biogeography, which provide important insights into community assembly processes. Mountain ecosystems provide informative systems for examining how biodiversity is distributed and identifying the mechanisms underlying those patterns. However, most of the existed studies only focused on plants, birds, and microbes, while little attention has been paid on amphibians, especially tadpoles. In the present study, we explored the elevational patterns of multiple facets of tadpole diversity and the community assembly mechanisms in temperate montane streams of Mount Emei, China. The taxonomic, functional, and phylogenetic diversity of tadpole assemblages in montane streams were quantified. Their elevational patterns were investigated using first and second-order polynomial regression analyses. The microhabitat determinants of these patterns were assessed by ordinary least squares models and hierarchical partitioning analyses. The phylogenetic tree of tadpoles and the Eucliden distance of traits between tadpoles were constructed. They were subsequently used to calculate the standardized effect size of mean pairwise phylogenetic and functional distances, and to speculate the tadpole assembly rules. Our results indicated that the Faith's PD and the standardized effect size of Faith's PD had hump-shaped responses to elevation, while the relationships between elevation and observed taxonomic diversity, observed functional diversity, and the standardized effect size of functional diversity were not significant. Interestingly, these patterns were determined by microhabitat variables, such as water conductivity, river width, water depth, and substrate type. Mean pairwise phylogenetic distance also showed hump-shaped correlations with the elevational gradient. Tadpole functional and phylogenetic structures were more clustered in low and high elevational streams, suggesting that environmental filtering was the main driver. At mid-elevations, functional and phylogenetic structures were overdispersal, indicating that limiting similarity plays a dominant role in shaping the tadpole assemblages.